Volume 1A: Abdominal Aortic Aneurysms; Active and Reactive Soft Matter; Atherosclerosis; BioFluid Mechanics; Education; Biotran 2013
DOI: 10.1115/sbc2013-14791
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Open Source Framework for the Simulation of Blood Flow in Rigid and Deformable Vessels

Abstract: SUMMARYWe discuss in this paper the validation of an open source framework for the solution of problems arising in hemodynamics. The proposed framework is assessed through experimental data for fluid flow in an idealized medical device with rigid boundaries and a numerical benchmark for flow in compliant vessels. The core of the framework is an open source parallel finite element library that features several algorithms to solve both fluid and fluid-structure interaction problems. The numerical results for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 45 publications
(115 reference statements)
1
48
0
Order By: Relevance
“…except in the convergent where the simulated pressure difference overestimates almost all the measurements. The reason for this overestimation is explained in [16]. Figure 2 shows that even mesh 1200k has a sufficient level of refinement to obtain numerical results in excellent agreement with the measurements in terms of average quantities, despite its h avg being roughly 20 times larger than the Kolmogorov length scale at Re t D 3500 (Tables I and II).…”
Section: Case Re T D 3500mentioning
confidence: 81%
See 2 more Smart Citations
“…except in the convergent where the simulated pressure difference overestimates almost all the measurements. The reason for this overestimation is explained in [16]. Figure 2 shows that even mesh 1200k has a sufficient level of refinement to obtain numerical results in excellent agreement with the measurements in terms of average quantities, despite its h avg being roughly 20 times larger than the Kolmogorov length scale at Re t D 3500 (Tables I and II).…”
Section: Case Re T D 3500mentioning
confidence: 81%
“…All the computational results presented in this article have been performed with LifeV [15], an open-source library of algorithms and data structures for the numerical solution of partial differential equations with high-performance computing techniques. In [16], we validated one Navier-Stoker solver implemented in LifeV with DNS up to Reynolds number 3500 and showed that a properly refined mesh is able to capture accurately the average flow features observed in the experiments. The LES technique used in this article makes the simulation of higher Reynolds numbers computationally affordable without sacrificing accuracy.…”
Section: Software and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the lattice Boltzmann method [10], which had difficulties to estimate meaningful velocity profiles in this complex test case and exhibited a large dependency on the lattices orientation, all other works reported flow averages in good agreement with the experimental quantitative data. DNS simulations performed on the open platform LifeV in [9] yielded surprisingly good results with coarse grids. However, for some transitional Reynolds number values, results were unstable and reported to depend on the numerical scheme and on the size of the computational domain.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, none of the CFD benchmark participants obtained results in agreement with the in vitro measurements for Reynolds numer (Re) 3500, although good agreement and excellent CFD results have been reported by multiple authors retrospectively. [12][13][14][15] The FDA nozzle benchmark model remains highly relevant for biomedical problems and our aim was to further validate the open-source CFD solver Oasis 16 that we have extensively used to study turbulent-like cardiovascular flows. [17][18][19][20][21][22][23] We focus on the flow at Re = 3500, which is in the particularly challenging transitional flow regime, for which the in vitro experiments displayed the least variability.…”
mentioning
confidence: 99%